Design, Optimization and Evaluation of Nanofibers Containing NSAID for Controlled Drug Delivery System - Chandira, Rajappa Margret; Pethappachetty, Palanisamy; Narayanan, Geetha Rani; Samy, Dominic Antony (Asian Journal of Biological and Life Sciences)
In the present research work, an attempt was made to develop nanofiber patches for piroxicam by using the polymers such as Ethycellulose, PVP. The advantages of nanofibers include the production of nanofibers layers from various polymers, and the incorporation of medications or growth factors into different nanofibers layers for wound care management. Piroxicam is a waterinsoluble drug, its shows high first-pass metabolism and hence an attempt was made to enhance solubility, to improve bioavailability and reduce toxicity. The physicochemical characterization for a pure drug such as organoleptic properties, spectral analysis UV spectroscopic studies, ATR-FTIR and DSC, was investigated and confirmed. Preparation of drug-loaded nanofibers patch (NFs) by Electrospinning process coupled layer-by-layer assembly method. The prepared nanofibers were analyzed for surface morphology by Scanning electron microscopy at different magnifications and evaluated the entrapment efficiency of drug-loaded nanofiber showing that the fibre formed with a smooth surface morphology and was spherical at 300nm. The prepared patches were subjected to evaluate the percentage of moisture content, tensile strength, swelling index, and in vitro diffusion studies for up to 12 hr. The stability study for the optimized nanofiber patch formulation was conducted for three months. Electrospun drug-loaded fibre patches could be a potential strategy in the lookout for a new platform with high drug and transdermal enhancer compatibility.
Keywords: Diffusion studies; Electrospinning; Magnification; Nanofibers; Transdermal patches.